PERUBAHAN NILAI NILAI BUDAYA DALAM PROSES MODERNISASI DI INDONESIA - Yuhasnil, Yuhasnil (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Along with the rapid flow of modernization, the changes that occur in all aspects of people's lives are increasingly inevitable. Not only does this change occur within the scope of social structures and social institutions but also in the fields of ethics, morals, and cultural values of the community. Cultural values are interpreted as something abstract that is used as a guide and general principles in acting and behaving. Changes occur in the form of culture such as ideas, values, norms, rules, activities and patterns of human actions in society and objects produced by humans. In the current era of globalization which is marked by the revolution of science, technology, information and telecommunications sector, it also significantly influences changes in the culture like the values and governance of people's lives. The transformation in determining accelerative changes for some parties may result in cultural lag and can also be in the cultural shock